2014
DOI: 10.1037/a0034840
|View full text |Cite
|
Sign up to set email alerts
|

Gestalt principle use in college students, children with autism, toddlers (Homo sapiens), and cotton top tamarins (Saguinus oedipus).

Abstract: The use of Gestalt principles of proximity, similarity, and closure to recognize objects by configural superiority was examined in college students, low- and high-functioning children with autism, toddlers, and adult cotton top tamarin monkeys. At issue was whether the monkeys showed differences from humans in perceptual processing and whether they showed any similarities with clinical or developmental groups. The method required a pointing response to discriminate an odd item in a 4-item visual display. All s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
1
9
0
2
Order By: Relevance
“…While this research highlights the potential limits of the rodent as a pre‐clinical model for the human visual system, it further points to the importance of cross‐species comparisons of perceptual phenomenon evident in human vision. Taken at face value, the current result suggests that only species most closely related to humans (that is old world primates) show a clear configural superiority effect (Neiworth et al ., ). Again, however, this pattern of results should be viewed as an inspiration to further research rather than offering a definitive conclusion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While this research highlights the potential limits of the rodent as a pre‐clinical model for the human visual system, it further points to the importance of cross‐species comparisons of perceptual phenomenon evident in human vision. Taken at face value, the current result suggests that only species most closely related to humans (that is old world primates) show a clear configural superiority effect (Neiworth et al ., ). Again, however, this pattern of results should be viewed as an inspiration to further research rather than offering a definitive conclusion.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, when animals had learned the discrimination that consisted of just lines differing in their orientation (Parts), they were also impaired when switched to the configuration of edges (whole stimuli). Interestingly this pattern of performance is qualitatively similar to that seen in Pigeons (Kelly & Cook, ), New World Monkeys (Neiworth et al ., ) and a severe visual form agnosia patient who suffered damage to higher areas of the ventral visual stream (de‐Wit et al ., ). This qualitative similarity could suggest that rodents lack some of the higher visual areas that might be necessary for this Configural Superiority Effect (Kubilius et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cotton-top tamarins showed no global bias regardless of the element density. Neiworth et al (2014) demonstrated that typically developing 3to 5-year-old children perceive figures by applying similar Gestalt principles to adults. In contrast, autistic children had difficulties in viewing global aspects of hierarchical stimuli (Brosnan et al, 2004), similar to tamarins, and they also had difficulties in viewing emergent Gestalt, suggesting that their visual systems lack higherlevel processing using Gestalt principles.…”
Section: Discussionmentioning
confidence: 99%
“…However, several other comparative studies have reported contradictory results. For example, Neiworth et al (2014) found that cotton-top tamarins discriminated diagonal lines less well when presented within a congruent context than presented alone. Talpos et al (2016) also reported a similar disruptive effect of congruent context in rats, implying that the perception of emergent Gestalts differs among mammals.…”
mentioning
confidence: 99%
“…Существует много исследований, посвященных формированию понятий и категоризации у приматов (Fagot, Maugard 2013;Merritt et al 2011;Smith et al 2010;Vonk 2003 и др. ); при этом показаны разные принципы организации категорий у приматов разных таксономических групп (Couchman et al 2010;Katz, Wright 2021;Mansouri et al 2020;Neiworth et al 2014). Однако нет работ, позволяющих с использованием единого методического подхода количественно оценить способность на основании отдельных фактов сделать вывод об общих свойствах подкрепляемых объектов (индуктивная форма мышления), а также способность на основании понимания правила в одном условии задачи сделать вывод в остальных условиях по аналогии (дедуктивная форма мышления) у разных видов приматов.…”
Section: Introductionunclassified